2023
DOI: 10.3390/microorganisms11071666
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability in Prevalence Rates of Members of the Borrelia burgdorferi Species Complex in Ixodes ricinus Ticks in Urban, Agricultural and Sylvatic Habitats in Slovakia

Abstract: Lyme borreliosis (LB) is the most prevalent tick-borne human infection in Europe, with increasing incidence during the latest decades. Abundant populations of Ixodes ricinus, the main vector of the causative agent, spirochetes from the Borrelia burgdorferi sensu lato (Bbsl) complex, have been observed in urban and suburban areas of Europe, in general, and Slovakia, particularly. Understanding the spread of infectious diseases is crucial for implementing effective control measures. Global changes affect contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The prevalence and diversity of species of the B. burgdorferi ( s.l .) complex in questing ticks and their associations with different reservoir hosts are relatively well-documented ( Stanko et al, 2022 ; Kazimírová et al, 2023 ). Small wild rodents have been identified as reservoirs for Borrelia afzelii and Borrelia bavariensis , songbirds (mainly blackbirds and thrushes) as reservoirs for Borrelia garinii and Borrelia valaisiana , and lizards as reservoirs for Borrelia lusitaniae .…”
Section: Tick Borne Pathogens Vectors Reservoir Hosts and Knowledge Gapsmentioning
confidence: 99%
“…The prevalence and diversity of species of the B. burgdorferi ( s.l .) complex in questing ticks and their associations with different reservoir hosts are relatively well-documented ( Stanko et al, 2022 ; Kazimírová et al, 2023 ). Small wild rodents have been identified as reservoirs for Borrelia afzelii and Borrelia bavariensis , songbirds (mainly blackbirds and thrushes) as reservoirs for Borrelia garinii and Borrelia valaisiana , and lizards as reservoirs for Borrelia lusitaniae .…”
Section: Tick Borne Pathogens Vectors Reservoir Hosts and Knowledge Gapsmentioning
confidence: 99%
“…of the spotted fever group infections in Ixodes ricinus collected in Central France from two different habitats (pasture vs woodland) (Halos et al 2010). Another study reported differences in Borrelia burgdorferi prevalences between urban/suburban habitats and natural/agricultural in Slovakia (Kazimírová et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal surveys are essential to visualise tick-borne pathogens occurrence fluctuations but also potential emergences, although they can be limited due to resource and time-consuming limitations (Sormunen et al 2018). Several studies demonstrated how temporal trends affect the occurrence of pathogens from several tick species in different countries (Takken et al 2017;Keesing et al 2021;Tran et al 2022;Foster et al 2022;Kazimírová et al 2023;Belkahia et al 2017;Chvostáč et al 2018;Coipan et al 2013;Reye et al 2010). In France, a three-years study on Ixodes ricinus-borne pathogens reported temporal fluctuations of prevalences of several common and less common TBP at the month, season and year scales (Lejal et al 2019a).…”
Section: Introductionmentioning
confidence: 99%